1995
DOI: 10.4049/jimmunol.155.6.2938
|View full text |Cite
|
Sign up to set email alerts
|

Role of the VLA-4 molecule in T cell costimulation. Identification of the tyrosine phosphorylation pattern induced by the ligation of VLA-4.

Abstract: The very late activated Ag (VLA) molecules not only mediate T cell adhesions, but also provide costimulation in a TCR/CD3-dependent manner. However, little is known about the signals mediated by the ligation of VLA molecules. Previous work from our laboratory identified a 105-kDa protein that is predominantly phosphorylated on tyrosine residue upon engagement of VLA-4 in a human T lymphoblastic cell line, H9, and in peripheral T cells. In the present study, we have shown that the A and B epitope of VLA-4 plays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Importantly, α4β1 expression enriched for intact and replication-competent proviruses in all samples tested and may represent an interesting addition to previously described flow cytometry panels aimed at isolating HIV-infected cells 83 . The combination of α4 and β1 integrins, also known as the adhesion molecule VLA-4, is involved in trafficking of immune cells to inflammatory sites as well as in T cell co-stimulation 84 . It was recently demonstrated that expression of VLA-4 on resting CD4+ T cells favors their susceptibility to HIV infection in vitro 85 suggesting that VLA-4 may contribute to the reseeding of the reservoir by promoting the migration of resting CD4+ T cells to inflammatory tissues and facilitating their de novo infection during ART 86,87 .…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, α4β1 expression enriched for intact and replication-competent proviruses in all samples tested and may represent an interesting addition to previously described flow cytometry panels aimed at isolating HIV-infected cells 83 . The combination of α4 and β1 integrins, also known as the adhesion molecule VLA-4, is involved in trafficking of immune cells to inflammatory sites as well as in T cell co-stimulation 84 . It was recently demonstrated that expression of VLA-4 on resting CD4+ T cells favors their susceptibility to HIV infection in vitro 85 suggesting that VLA-4 may contribute to the reseeding of the reservoir by promoting the migration of resting CD4+ T cells to inflammatory tissues and facilitating their de novo infection during ART 86,87 .…”
Section: Discussionmentioning
confidence: 99%
“…Integrins including alpha-4 integrin (VLA-4) are so called bi-directional signalling molecules that connect to the cytoskeleton and activate intracellular signalling pathways [10]. Ligation of VLA-4, which forms an essential part of the immunological synapse, was demonstrated to provide costimulatory signals to T cells [11][12][13] and anti-VLA-4 therapy was suggested to modulate the activation of lymphocytes in experimental animal models of MS [25]. Accordingly, direct effects of Natalizumab on the homeostasis of Tregs and their immunobiological functions appear feasible.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to bead-based suppression assays we used allogeneic immature and mature DC to challenge T effector cells. Since VLA-4 is part of the immunological synapse and has been suggested to be involved in costimulation [11][12][13] we first investigated whether Natalizumab influences the outcome of DC-T cell encounters by modulating T cell proliferation. However, Natalizumab (20 mg/ml) did not impact the percentage of proliferating T cells in response to immature DC (23,96+/ 210,57 vs. 24,58+/214,02) or mature DC (39,324+/214,77 vs. 39,178+/216,67) as determined by CFSE dilution assays (n = 5, Figure 4c).…”
Section: Natalizumab Does Not Restore the Impaired Suppressive Functi...mentioning
confidence: 99%
See 1 more Smart Citation